A public data set of walking full-body kinematics and kinetics in individuals with Parkinson’s disease - Shida, Thiago Kenzo Fujioka; Costa, Thaisy Moraes; de Oliveira, Claudia Eunice Neves; de Castro Treza, Renata; Hondo, Sandy Mikie; Los Angeles, Emanuele; Bernardo, Claudionor; dos Santos de Oliveira, Luana; de Jesus Carvalho, Margarete; Coelho, Daniel Boari (Frontiers in Neuroscience, 2023)
Background To our knowledge, there is no Parkinson’s disease (PD) gait biomechanics data sets available to the public. Objective This study aimed to create a public data set of 26 idiopathic individuals with PD who walked overground on ON and OFF medication. Materials and methods Their upper extremity, trunk, lower extremity, and pelvis kinematics were measured using a three-dimensional motion-capture system (Raptor-4; Motion Analysis). The external forces were collected using force plates. The results include raw and processed kinematic and kinetic data in c3d and ASCII files in different file formats. In addition, a metadata file containing demographic, anthropometric, and clinical data is provided. The following clinical scales were employed: Unified Parkinson’s disease rating scale motor aspects of experiences of daily living and motor score, Hoehn & Yahr, New Freezing of Gait Questionnaire, Montreal Cognitive Assessment, Mini Balance Evaluation Systems Tests, Fall Efficacy Scale-International–FES-I, Stroop test, and Trail Making Test A and B. Results All data are available at Figshare (<ext-link ext-link-type="uri" xlink:href="https://figshare.com/articles/dataset/A_dataset_of_overground_walking_full-body_kinematics_and_kinetics_in_individuals_with_Parkinson_s_disease/14896881" xmlns:xlink="http://www.w3.org/1999/xlink">https://figshare.com/articles/dataset/A_dataset_of_overground_walking_full-body_kinematics_and_kinetics_in_individuals_with_Parkinson_s_disease/14896881). Conclusion This is the first public data set containing a three-dimensional full-body gait analysis of individuals with PD under the ON and OFF medication. It is expected to contribute so that different research groups worldwide have access to reference data and a better understanding of the effects of medication on gait.